2019
DOI: 10.1091/mbc.e18-08-0510
|View full text |Cite
|
Sign up to set email alerts
|

Lowe syndrome–linked endocytic adaptors direct membrane cycling kinetics with OCRL inDictyostelium discoideum

Abstract: Mutations of the inositol 5-phosphatase OCRL cause Lowe syndrome (LS), characterized by congenital cataract, low IQ, and defective kidney proximal tubule resorption. A key subset of LS mutants abolishes OCRL’s interactions with endocytic adaptors containing F&H peptide motifs. Converging unbiased methods examining human peptides and the unicellular phagocytic organism Dictyostelium discoideum reveal that, like OCRL, the Dictyostelium OCRL orthologue Dd5P4 binds two proteins closely related to the F&H p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…Both macropinosome and phagosome membranes initially contain high levels of PI(3,4)P 2 . PI(3,4)P 2 is generated by the rapid de-phosphorylation of PI(3,4,5)P 3 by the PI-5 phosphatase called Oculocerebrorenal syndrome of Lowe (OCRL), during and immediately following cup closure (Dormann et al, 2004;Li et al, 2018;Loovers et al, 2007;Luscher et al, 2019). On phagosomal membranes PI(3,4)P 2 content peaks immediately following cup closure and is gradually lost over time (Dormann et al, 2004).…”
Section: The Nascent Macropinosome/ Phagosomementioning
confidence: 99%
“…Both macropinosome and phagosome membranes initially contain high levels of PI(3,4)P 2 . PI(3,4)P 2 is generated by the rapid de-phosphorylation of PI(3,4,5)P 3 by the PI-5 phosphatase called Oculocerebrorenal syndrome of Lowe (OCRL), during and immediately following cup closure (Dormann et al, 2004;Li et al, 2018;Loovers et al, 2007;Luscher et al, 2019). On phagosomal membranes PI(3,4)P 2 content peaks immediately following cup closure and is gradually lost over time (Dormann et al, 2004).…”
Section: The Nascent Macropinosome/ Phagosomementioning
confidence: 99%
“…OCRL is an inositol polyphosphate 5-phosphatase that hydrolyzes the 5-phosphate of PI(4,5)P2 into PI4P ( Prosseda et al, 2017 ). Interestingly, a recent study in D. discoideum has shown that OCRL-like protein of D. discoideum , Dd5P4, is recruited to the CV membrane upon the kiss-and-run exocytic event ( Luscher et al, 2019 ). Therefore, it is possible that the exocytic function of ORCL contributes to the pathological process of Lowe syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…SecA is therefore necessary for CV fusion to the PM and water discharge. A recent study suggested that PI(4,5)P2 regulates the trafficking of the CV to the fusion site and cells with a defect in Dd5P4, the enzyme which uses the 5-phosphates of PI(4,5)P2 as substrate, displayed inefficient CV fusion ( Luscher et al, 2019 ).…”
Section: Contractile Vacuoles and Exocytosis In Dictyosteli...mentioning
confidence: 99%